Shariah Stock Emitent Efficiency Strategy in Digital Era: Application of DEA Super-Efficiency and Interpretive Structural Modeling - Aam; Irman Firmansyah (Review on Islamic Accounting, 2022)
This study aims to determine the level of efficiency in companies listed on the Jakarta Islamic Index today and find strategies that can be used to achieve optimal levels of efficiency through the use of digital. Analysis using DEA Super Efficiency and Interpretative Structural Modeling. The results show that companies that are consistent on JII have a greater efficiency score than companies that are not consistent, thus showing the importance of a company having an optimal level of efficiency in order to be consistently listed on JII. Based on the sample used, the average performance PT Indofood Sukses Makmur is better than other companies that are ranked in the top 5 for three consecutive years with an efficiency score of 1. In addition, efficiency results that can be said to be very good do not guarantee the company's constant conditions in terms of production of inputs and outputs in the form of RTS expected by the company. The average company experiences conditions that tend to be unstable in terms of production. So, it needs attention from management to increase input production capacity for the desired output. Information technology is one of the solutions to achieve an optimal level of efficiency, so ISM found that the best strategy is to prepare sufficient human resources and budget to use information technology in running its business, then the next strategy is to place IT in the main areas of the business so that IT can maximally used.